Steady and transient response of triangular TLPS under random wave loads - Chandrasekaran S.; Gaurav; Srivastava S. (My University, 2025)
Considerable effort has been put into understanding the intense nonlinear response shown by tension leg platforms (TLPs) after they were first observed in a model test of the Hutton TLP in the North Sea in 1980s. This response is broadly of two kinds namely: (i) steady state response or springing; as well as (ii) transient response or ringing. Springing is a consequence of second order wave effects at the sum frequencies while ringing is due to passage of high, steep waves. Many studies have been reported on square TLPs but no specific study on triangular configuration TLPs has been attempted yet. The objective of this paper is to study transient and steady state response of triangular TLPs under random wave loads. Analytical studies conducted show that springing was found to be sub-harmonic resonance while illustrating the possible loading patterns that can trigger ringing response in TLPs. It is interesting to know that on account of their triangular configuration, these TLPs tend to possess higher rigidity against springing and ringing forces thus making it as a safe alternative for deepwater oil explorations.